(untitled) (CIPEEX, 2022)
MUCH HAS BEEN DISCUSSED ABOUT THE FACT THAT BRAZILIAN COMPANIES SOMETIMES ADOPT THE FAMILY HOLDING METHOD, WHOSE PURPOSE IS TO FACILITATE THE HEREDITARY SUCCESSION OF ASSETS IN THE EVENT OF THE DONOR’S DEATH, PLANNING IN ADVANCE AND IN A SATISFACTORY MANNER. THIS IS BECAUSE ALL SUCCESSION RULES WILL ALREADY BE DEFINED IN THE HOLDING COMPANY’S ARTICLES OF ASSOCIATION, PREVENTING FAMILY ASSETS FROM GOING THROUGH A LONG INVENTORY PROCESS, AND WITHOUT THE NEED TO INTERRUPT THE ACTIVITIES OF FAMILY BUSINESSES, WHEN APPLICABLE. THUS, THE PRESENT STUDY HAD AS A PROBLEM: IS SUCCESSION PLANNING IN THE FAMILY HOLDING IMPORTANT FOR A COMPANY TO SUCCEED WITH ITS FUTURE ADMINISTRATORS? THE MAIN OBJECTIVES WERE: TO UNDERSTAND THE CONCEPT OF FAMILY PROPERTY, LEGISLATION, PRINCIPLES AND HISTORY; IDENTIFY STAGES OF SUCCESSION PLANNING THAT LEAD TO THE SUCCESS OF COMPANIES WITH IMMUTABLE RULES FROM GENERATION TO GENERATION; AND STUDY IN DETAIL A SPECIFIC CASE TO SEEK TO ACHIEVE THE MERITS OF THE FAMILY HOLDING. AS A RESULT, THE HOLDING COMPANY CAN BE INCORPORATED IN THE FORM OF A LIMITED LIABILITY COMPANY, AND CAN ALSO BE PURE OR MIXED. THE HOLDING COMPANY HAS NO LEGAL NATURE, IT IS A CORPORATION, AND CAN ALSO ACT IN THE AREA OF €‹€‹SERVICE PROVISION, SERVING AS OUTSOURCING. IN ADDITION, THE HOLDING COMPANY HAS BEEN ADOPTED BY BRAZILIAN COMPANIES, SINCE ITS SUCCESSION RULES ARE ALREADY PRESENT IN THE ARTICLES OF ASSOCIATION, SO ITS PURPOSE IS TO CONTROL THE ASSETS OF INDIVIDUALS OF THE SAME FAMILY, MAKING THE HEIRS DOMINATE THE POSITION OF PARTNERS. IT IS CONCLUDED THAT THE PLANNING FOUND IN THE CIVIL CODE IS A PROCESS OF DECISIONS IN ADVANCE, WHICH CAN LEAD TO SIGNIFICANT ADVANTAGES, SUCH AS: FACILITATION, ASSET PROTECTION AND TAX PLANNING. IN ADDITION TO THE ADVANTAGES, IT ALSO HAS DISADVANTAGES, WHICH MUST BE ANALYZED BEFORE ITS CONSTITUTION. THE CREATION OF THIS COMPANY WITHOUT PROPER FISCAL AND FINANCIAL PLANNING CAN LEAD TO DISADVANTAGES SUCH AS: CAPITAL GAIN TRIBULATION RELATED TO THE SALE OF PARTICIPATION IN ASSOCIATED COMPANIES. THEREFORE, IT SOUGHT TO ELUCIDATE IN THE COURSE OF THE WORK THAT THE HOLDING IS THE PASSPORT FOR SMALL, MEDIUM AND LARGE COMPANIES TO ACHIEVE LIFELONG SUCCESS IN THE FAMILY ENVIRONMENT, PROFESSIONALIZING ITS PARTNERS OVER THE GENERATIONS THROUGH MENTORING, AND THAT IF FOLLOWED IN A DETAILED EACH STEP, THE COMPANY WILL HAVE MANY ADVANTAGES OVER ITS COMPETITORS, FOR EXAMPLE, IN TAX PLANNING, BUT IF NOT FOLLOWED PROPERLY, IT COULD BE CATASTROPHIC AS THE WAY TO OPERATIONALIZE THE DIFFERENTIATED TREATMENTS OF THE VARIOUS SECTORS OF THE ECONOMY, MAINLY DUE TO THE LACK OF KNOWLEDGE SPECIFIC TO THE REALITY OF EACH SECTOR. THE METHODOLOGY APPLIED WAS QUALITATIVE BASED ON BIBLIOGRAPHIES, BOOKS AND ARTICLES ALREADY PUBLISHED BY DIFFERENT AUTHORS, JUDGED AND CASE STUDIES.